PENGARUH FRAUD DIAMOND, FINANCIAL STABILITY TERHADAP PENDETEKSIAN FRAUDULENT FINANCIAL STATEMENT - Amrullah, Rahadian; Wulandari, Putri (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
This study aims to analyze and determine the effect of fraud diamond and financial stability on fraudulent financial statements. The technique used in determining the data for this study uses purposive sampling technique and can be used as many as 28 samples of banking companies. For data processing, the SPSS software application version 24 was used. The results of the study showed that pressure had a negative effect on fraudulent financial statements and was rejected. Opportunity had a negative effect on fraudulent financial statements and was rejected. Rationalization had a positive effect on fraudulent financial statements and was accepted. Capability had a negative effect on fraudulent financial statements and was rejected. Financial stability had a positive effect on fraudulent financial statements and was accepted